DEPICTION OF WOMEN IN THE PAINTINGS OF PAKISTANI ARTIST, IQBAL HUSSAIN - Jessani, Hinna (PEOPLE: International Journal of Social Sciences, 2018)
From 1970’s onwards, works of many Pakistani artists have focused on the themes associated with the general masses including traditions, displacement, gender, ideology (Hashmi & Ata-Ullah, 2009, p. 68), social issues and lately, terrorism. Following this trend, paintings of artist Iqbal Hussain remain significant in advocating the realities of the marginalized class of society. This paper analyses Hussain’s depiction of prostitute women and their hardships, who are considered as a symbol of disgrace in a Muslim country like Pakistan, which is moving towards religious extremism. The research shows that being a son of a courtesan, Hussain through his paintings represents the image and problems of dancing girls and courtesans of Shahi Mohalla, Lahore. These women were considered as the custodians of artistic traditions in the Mughal era (Ghauri, 2003). However, over the time they lost their status in Pakistan. In this context, Hussain’s work attempt to regain the respect for these women in society by advocating their everyday struggles among the national and international audience. This study is a secondary research. It draws upon the examination of diverse writings on art literature, newspaper archives, books and interpretation of a variety of Hussain’s paintings. The research on Hussain’s work explores further research avenues related to the role of women and impact of Islamization in Pakistan, historical analysis of different political governments towards the prostitutes in Pakistan and the idea of 'shame' and 'honor' in the South Asian arts, literature, and cinema.